2022
DOI: 10.1158/0008-5472.can-21-2269
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery of miR-122 Inhibits Colorectal Cancer Liver Metastasis

Abstract: Liver metastasis is a leading cause of cancer morbidity and mortality. Thus, there has been strong interest in the development of therapeutics that can effectively prevent liver metastasis. One potential strategy is to utilize molecules that have broad effects on the liver microenvironment, such as miR-122, a liver-specific miRNA that is a key regulator of diverse hepatic functions. Here we report the development of a nanoformulation miR-122 as a therapeutic agent for preventing liver metastasis. We engineered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Their research found that miR-122 transmission was linked to the downregulation of essential genes implicated in the inflammatory routes that lead to cancer metastasis, namely several pro-inflammatory factors, matrix metalloproteinases, and other extracellular matrix breakdown enzymes. The liver is more receptive to an antitumor immunological reaction as a result of Gal-LCP miR-122 therapy because of its enhanced CD8 + /CD4 + T-cell ratio and reduced cell-infiltrated immunosuppression [ 103 ]. Additionally, perfluoropentane/C9F17-PAsp(DET)/miR-122/poly(glutamic acid)-g-MeO-poly(ethylene glycol) (PGA-g-mPEG) ternary nanodroplets (PFP-TNDs/miR-122), were created by Guo et al to transfer miR-122 for the treatments of HCC.…”
Section: Mir-122 and Cancer Stem Cellmentioning
confidence: 99%
“…Their research found that miR-122 transmission was linked to the downregulation of essential genes implicated in the inflammatory routes that lead to cancer metastasis, namely several pro-inflammatory factors, matrix metalloproteinases, and other extracellular matrix breakdown enzymes. The liver is more receptive to an antitumor immunological reaction as a result of Gal-LCP miR-122 therapy because of its enhanced CD8 + /CD4 + T-cell ratio and reduced cell-infiltrated immunosuppression [ 103 ]. Additionally, perfluoropentane/C9F17-PAsp(DET)/miR-122/poly(glutamic acid)-g-MeO-poly(ethylene glycol) (PGA-g-mPEG) ternary nanodroplets (PFP-TNDs/miR-122), were created by Guo et al to transfer miR-122 for the treatments of HCC.…”
Section: Mir-122 and Cancer Stem Cellmentioning
confidence: 99%
“…[19][20][21] They play multiple roles in various physiological processes, including neovascularization, immune regulation, and the stress response. 22,23 Therefore, it is possible that miRNAs are also involved in acute rejection during VCA. To this end, we sequenced the miRNAs in control and transplanted muscle tissues in a rodent model of VCA, and identified 28 differentially expressed miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…A nanoparticle-based delivery of these molecules effectively mediates RNA interference in cancer cells, and nano-carriers can be optimized to meet the therapeutic requirements of a specific disease (reviewed in ref. 65 ), such as colorectal cancer liver metastasis ( 66 ).…”
Section: Discussionmentioning
confidence: 99%